Invasive Alien Plant species (IAPs) for Sustainable Pest Management: A Review - Chhetri, Til Kumari; Thapa, Raj Kumar; Bhattarai, Hari Datta (Journal of Plant Resources, 2025)
Invasive alien plants (IAPs) threaten biodiversity and agricultural productivity via disruption of ecological processes. Managing IAPs is challenging as they spread across Nepal. Prevention is now challenging, and eradication is only feasible in small, managed areas. IAPs have great potential as sustainable source of bio-pesticides. The use of synthetic pesticides for controlling agricultural pests, household insects, and mosquitoes has significant drawbacks. They are expensive, persist long-term in soil and food, negatively impact human health and environment, and lead to pest resistance. Hence, IAPs can be the alternative for synthetic pesticides. This review was conducted to examine the insecticidal activities of Nepal’s IAPs to generate alternative solutions for pest and IAPs management by utilizing them. The study involved a comprehensive literature review of the insecticidal properties of 30 IAPs of Nepal. Data were collected from various published studies and the focus was on identifying the plant parts used for formulations, the insect and their stages targeted, and the overall effectiveness of different extract formulations. Among the 30 IAPs of Nepal, 18 species have been studied at many countries for their insecticidal properties against various insects, including mosquitoes and agricultural pests. Most studies were conducted in India and Nigeria. Leaves were the most frequently used plant part for formulations. The larval stage of insects was the preferred stage for studying insecticidal properties. Essential oils were found to be more effective than other extract formulations. All studies demonstrated toxicity to different insects at different level. IAPs of Nepal possess insecticidal activity against harmful insects and pests, offering potential for sustainable pest management.